INOVAÇÃO EM ARRANJO PRODUTIVO LOCAL: UMA VISÃO SOB A ÓTICA COLABORATIVA - Rezende, Geison Rolf (2020)
Discussions about innovation have intensified in the last years, whether in the organizational scope or in the academic scope. Thus, also the need for collaboration for innovation has received special attention, especially from researchers in the area. In this context, this study aimed to analyze the process of collaboration for innovation of companies of the Local Productive Arrangement (LPA) of clothing, in the city of Cianorte-PR, from the perspective of the representatives of the organizations. This is a descriptive study, with a quantitative approach, with data collection through selfadministered forms, which were sent to the managers of the organizations, objects of this study. The sample was non-probabilistic and by adherence, consisting of 52 forms. For the treatment and analysis of these data, we used the mean and standard deviation, Cronbach's Alpha, Cluster Analysis and Pearson’s Correlation Analysis. Based on the results obtained, having its design through the objectives of this study, it was found that innovation is an aspect of relevance for the companies that are respondents to the LPA. It was also found through the results that the improvement of product quality and the maintenance of market share in which they operate were outstanding items. The analysis of collaboration can be understood to a greater degree between the companies that make up the production chain and its competitors, and the collaboration bonds of organizations is something that needs to be developed and disseminated. In addition to these factors, the main reasons that lead organizations to cooperate with each other are to reduce costs and risks linked to the innovation process. The companies in the sample were classified, according to their perspective of collaboration, into three groups (not very collaborative, collaborative and prone to collaborate), and the average perception differs significantly in relation to the sources and reasons for collaboration. The association between innovation and the reasons for collaboration is significant. The intervening factors used impacted on the association between innovation and collaboration only when considering the reasons for collaborating, but not when considering the sources of collaboration.